1976
DOI: 10.1002/hlca.19760590114
|View full text |Cite
|
Sign up to set email alerts
|

Pseurotin, a New Metabolite of Pseudeurotium ovalis STOLK Having an Unusual Hetero‐Spirocyclic System. (Preliminary Communication)

Abstract: The structure and absolute configuration of pseurotin (1), a new metabolite, isolated from culture filtrates of Pseudeurotium ovalis STOLK (Ascomycetes), has been shown to be 2‐[1′(S), 2′ (S)‐dihydroxhex‐3′‐ene‐yl]‐3‐methyl‐8(S)‐methoxy‐8‐benzoyl‐9(R)‐hydroxy‐(5S)‐1‐oxa‐7‐aza‐spiro[4.4]non‐2‐ene‐4, 6‐dione (1), by spectral data and chemical transformations, and by X‐ray analysis of its dibromo derivative 2 [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 11 publications
1
64
0
1
Order By: Relevance
“…Pseurotin A, first isolated from Pseudoeurotium ovalis [11] is a competitive inhibitor of chitin synthase, [14] and a neuritogenic agent. [23] Feeding experiments showed that pseurotin A is derived from one molecule of propionyl-coenzyme A, one molecule of phenylalanine and four molecules of malonyl-coen-A C H T U N G T R E N N U N G zyme A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseurotin A, first isolated from Pseudoeurotium ovalis [11] is a competitive inhibitor of chitin synthase, [14] and a neuritogenic agent. [23] Feeding experiments showed that pseurotin A is derived from one molecule of propionyl-coenzyme A, one molecule of phenylalanine and four molecules of malonyl-coen-A C H T U N G T R E N N U N G zyme A.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Together with 8-O-demethylpseurotin A (2) and synerazol (3), it was also isolated from A. fumigatus. [12,13,14] Azaspirene (4), with the same core structure, was obtained from A C H T U N G T R E N N U N G Neosartorya sp.…”
Section: Bioinformaticsmentioning
confidence: 99%
“…-The pseurotins are a small family of secondary microbial metabolites which have been isolated from cultures of Pseudeurotium ovalis STOLK. The isolation, spectral data, and chemical properties as well as biosynthetic studies on the main component, pseurotin A (l), have been already reported [2]. Pseurotin A (1) possesses a novel highly substituted l-oxa-7-azaspiro [4.4]nonane skeleton and five chiral centers.…”
Section: Synthetic Studies Towards Pseurotinmentioning
confidence: 98%
“…[66][67][68][69] Genome sequencing of Aspergillus fumigatus 70) has revealed a number of gene clusters that are predicted to encode for enzymes that constitute natural product biosynthetic pathways. The gene cluster responsible for the biosynthesis of pseurotin A (19) was predicted and identified by deleting or overexpressing a PKS-NRPS gene psoA in A. fumigatus Af293 71) (Table 1).…”
Section: Understanding Pseurotin Scaffold By Functional Analysis Of Tmentioning
confidence: 99%